Protestant missionary activity in Iran in the second half of 20th and the beginning of the 21st centuries - Tatyana V. Skrabanskaya (Вестник Свято-Филаретовского института)
The article is dedicated to the understudied issue of Protestant missionary activity in Iran in the context of social and political changes in the second half of the 20th and the beginning of the 21st centuries. Based on analytical reports of charitable and human rights organisations, testimonies of representatives of Iranian churches published in open sources, as well as a number of monographs devoted to the issue of Protestant denominations in Iran, this paper examines the main points of change in missionary strategy, including the practice of house churches, the prioritisation of direct mission and the abandonment of social missionary projects, the use of modern media and translations of liturgical texts into Persian. Special attention is given to the impact of the 1979 Islamic Revolution on the Christian mission in Iran. As a result of the analysis, the author comes to the conclusion that informal communities of believers, in particular, underground house churches, as mission actors, proved to be more effective than official institutions. The missionary practices used by house churches are based on the fact that all Christians are called to witness and imply considerable freedom of action on the part of missionaries. The withdrawal of foreign missionaries from the country, the rejection of proselytising and counter-missions greatly increased the credibility of Protestant missionaries and contributed to the success of the mission. The key importance of personal mission and witness by personal example is also pointed out, in particular the martyrdom of Pastors Mehdi Dibaj, Haik Hovsepian Mehr and other Iranian Christians who did not abandon their ministry even in the face of mortal danger.